Empowerment of Coffee Processing Business Actors of the Central Lawu Nature Lovers Group as a Form of Utilization of Local Commodities in Sukowidi Village, Panekan District, Magetan Regency - Alfi Rochmah; Yenny Febriana Ramadhan Abdi; Anam Choiroel; Dininurilmi Putri Suleman; Prajwalita Rukmakharisma Riski; Fitriyah Zulfa; Dini Nadhilah (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Sukowidi Village, located in Panekan District, Magetan Regency, is known as the largest coffee commodity-producing area. The sale of this coffee is one of the economic drivers for the residents of Sukowidi Village. Sukowidi Village already has a fairly active Central Lawu nature lovers group that can be an agent in overcoming coffee problems, but the lack of insight into entrepreneurship, food processing techniques, and marketing techniques is an obstacle to developing coffee. The UNS PKM Team will empower the group through proper coffee processing, and ready to be marketed as a form of utilization of local coffee commodities. The activities carried out are conducting entrepreneurship training and food industry management in order to provide direction in entrepreneurship and managing a coffee processing business. Furthermore, the UNS PKM Team also provides training and assistance on how to process coffee properly so that safe, hygienic, and halal products can be produced and are enjoyable to consume by the community. The introduction of tools is also carried out to support coffee processing activities, namely in the form of huller and pulper machines. The main objective of the community service is to create UMKM managed by members of the Lawu Tengah nature lovers group in Sukowidi Village with good quality according to good, safe and halal food processing procedures because the production process is free from non-halal additives, and attractive in terms of appearance, so that it can support halal tourism which the government is promoting. The results of this community service activity are that the nature lovers group is skilled in processing coffee, can operate huller and pulper machine processing equipment, can start implementing good, safe, halal food processing methods, and can become entrepreneurs. Keywords: Coffee, Social Entrepreneurship, Digital Marketing, Lawu